A Fairly Genuine Comment on Honest Opinion in New Zealand - Marten, Bevan (Victoria University of Wellington Law Review, 2005)
This paper discusses the defence of honest opinion in relation to New Zealand’s Defamation Act 1992. Two key issues are addressed: the place of the common law “public interest” requirement in the New Zealand context, and the concept of “genuineness” under section 10 of the Act. It is argued that the public interest requirement should be abolished, and that the relevant statutory provisions be redrafted to achieve this. The redraft would also clarify a potential flaw in the wording of the defence that may render it unavailable to some defendants who are quoting the opinions of others.